PERANAN SUBAK PULAGAN-KUMBA DALAM PENANGGULANGAN ALIH FUNGSI LAHAN PERTANIAN DI DESA TAMPAKSIRING, KECAMATAN TAMPAKSIRING, KABUPATEN GIANYAR, BALI - Darmanta, I Nyoman (Universitas Pendidikan Ganesha, 2013)
ABSTRACTThis current study aimed at describing : ( 1) Forms of agriculture shift land (2) The role and function of Subak Gede Pulagan-Kumba to reduce agriculture land shifted (3) The difficulties faced by Subak Gede Pulagan-Kumba in running owned role and function of Subak Gede Pulagan-Kumba to reduce shifted agriculture land. This sdudy was done in Subak Gede Pulagan-Kumba in Tampaksiring village, Tampaksiring District, Gianyar regency, Bali. The study was designed in form of descriptive-qualitative. The subjek of this study were used purposive sampling technique, and the informant of this study were : (1) Prajuru (Broad) of subak Gede Pulagan-Kumba, (2) Krama (members) of subak Gede Pulagan Kumba and (3) and peoples in Tampaksiring village which have agriculture land but do not the including as membersof subak. The data gathered in this study namely interview and documentation method. Technique analyse data which is used in this study is data analysis of descriptive-qualitative. Based on date found by researcher on 2007 until 2012 the shifted agriculture land that happened in region of subak Gede Pulagan-Kumba have reached number 5,47 hectare from wide of the overall of region of subak Gede Pulagan-Kumba for the width of 205 hectare or 2,7% from wide of the overall of region of subak Gede Pulagan-Kumba. The shifted agriculture land consist of several forms such as: housing of person, shop, place of effort, private sector clinic, livestock cage and school. Most dominating form is housing of person. Subak Gede Pulagan-Kumba have role and function as a traditional institution which hoped to reduce shifted agriculture land with the various law that this organitation have. The difficulties faced by Subak Gede Pulagan-Kumba to reduce shifted agriculture land were consist of two categories such as intern problem showed from the weakly legitimation that subak has to reduce shifted function and the wider authority which is members have as the owner of the land to manner their own. Then extern problems were growth of society development and economy also the higher of agriculture land sold.Key words: Subak, Shifted agriculture land function, Agriculture.